Predefined-Time Active Fault-Tolerant Control of Transport Aircraft Subject to Control Surface Failures - Li, Yu; Wang, Tianqi; Liu, Xiaoxiong; Wen, Chih-yung (IEEE transactions on aerospace and electronic systems, 2025)
This article presents a predefined-time (PdT)-based incremental backstepping with a PdT disturbance observer control scheme for transport aircraft. Based on this control scheme, an active fault-tolerant flight controller (AFTFC) is designed to achieve PdT fault-tolerant control under control surface failures. By constructing a nonlinear state transformation function, the damaged aircraft's attitude angles are restricted within a safe range. The designed AFTFC ensures that the damaged aircraft can robustly retrack its desired commands within a PdT with a bounded steady-state error, while the settling time is user-defined, which does not depend on the initial conditions or design parameters. More importantly, AFTFC also addresses the issue of robustness degradation due to state differentiation disturbances in traditional incremental control. Real-time simulation experiments are presented to verify the effectiveness of the designed AFTFC.